2017
DOI: 10.1038/srep45984
|View full text |Cite
|
Sign up to set email alerts
|

Co-grinding Effect on Crystalline Zaltoprofen with β-cyclodextrin/Cucurbit[7]uril in Tablet Formulation

Abstract: This work aimed to investigate the co-grinding effects of β-cyclodextrin (β-CD) and cucurbit[7]uril (CB[7]) on crystalline zaltoprofen (ZPF) in tablet formulation. Crystalline ZPF was prepared through anti-solvent recrystallization and fully analyzed through single-crystal X-ray diffraction. Co-ground dispersions and mono-ground ZPF were prepared using a ball grinding process. Results revealed that mono-ground ZPF slightly affected the solid state, solubility, and dissolution of crystalline ZPF. Co-ground disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…After the completion of the grinding process, the sample was formed into a pellet using a hydraulic press. The spectra were measured in the transmission mode. For the sample of the complex of βCD and the guest (compound Fc-1–Fc-5 or Ada-1 ): the grinding-induced liquid-assisted method was applied for the complex preparation. To the mixture of 5.0 × 10 –3 mmol of the guest and 5.0 × 10 –3 mmol of βCD (complex stoichiometry 1:1), 5 μL of pure water was added, and the solid was intensively grinded for 25 min. At first, the mixture had a form of slurry, but after the grinding process, it became a dry solid.…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the grinding process, the sample was formed into a pellet using a hydraulic press. The spectra were measured in the transmission mode. For the sample of the complex of βCD and the guest (compound Fc-1–Fc-5 or Ada-1 ): the grinding-induced liquid-assisted method was applied for the complex preparation. To the mixture of 5.0 × 10 –3 mmol of the guest and 5.0 × 10 –3 mmol of βCD (complex stoichiometry 1:1), 5 μL of pure water was added, and the solid was intensively grinded for 25 min. At first, the mixture had a form of slurry, but after the grinding process, it became a dry solid.…”
Section: Methodsmentioning
confidence: 99%
“…The ZPF polymorph, Form I showed an aqueous solubility of 0.019 mg/mL and was found in agreement with the solubility of 0.018 mg/mL, reported earlier by Li and coworkers. 34 The ZPF polymorph, Form II shows a 3-fold increase in the solubility (0.060 mg/mL) compared to Form I. The polymorph solubility data also correlates with the computed lattice energy differences, i.e., the more stable polymorph (Form I) is less soluble than the metastable polymorph, Form II.…”
Section: ■ Results and Discussionmentioning
confidence: 72%
“…Li et al recently reported the crystal structure of the anhydrous crystalline form (Form I) of zaltoprofen. 34 They also studied the effect of cogrinding of ZPF with β-cyclodextrin and cucurbit [7]uril on its solubility, dissolution rates, and compressibility properties. Herein, we report a new metastable polymorph (Form II) and three new cocrystals of nonsteroidal anti-inflammatory drug zaltoprofen identified from the rational coformer screening approach.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Standard methods for obtaining API complexes with CDs in solid form can be quite laborious and time consuming. For example, cogrinding of APIs with CDs is usually carried out in high-energy mills for one hour or longer [55][56][57][58]. On the basis of the results reported in this work, it should be possible to use low-energy cogrinding, which is desirable due to the simplicity and reduced production time.…”
Section: Discussionmentioning
confidence: 90%